Sistem Informasi Rumah Sakit - David Kolibu; Dety Mulyanti (Universitas Katolik Widya Karya Malang, 2023)
The hospital information system has become increasingly important due to the rapid development of technology. An effective information system can help manage patient data, medical records, doctor scheduling, medicine and medical equipment procurement, and facilitate hospital administration processes. This journal discusses the importance of hospital information systems, the benefits that can be gained, and the things that need to be considered in building and implementing an effective information system. Analysis of information system needs, information system development, training and utilization of the system, and information system maintenance are important factors to consider in building an effective system. With an effective and efficient information system, it is hoped that the quality of hospital services can be improved.